Prosthetic rehabilitation of nasomaxillary defect with TAD retained surgical obturator followed by hollow bulb definitive obturator and immediate lower denture - Wijaya, Agustinus Kenny; Barunawati, Sri Budi; Fransiscus Wihan Pradana; Suparyono Saleh (Indonesia Prosthodontic Association, 2024)
The integrity and functionality of the oral cavity may be compromised by nasomaxillary defects, such as speech, mastication, deglutition, and esthetics. Early prosthodontic rehabilitation can improve quality of life and lessen the psychological harm caused by the surgical treatment. A 70-years-old female patient was referred to the Department of Prosthodontics RSUP Dr. Sardjito Yogyakarta with chief complaints of nasal obstruction, and right-side swelling of the face. Extraoral examination revealed facial asymmetry due to swelling of the right buccal region. On intraoral examination, showing a large, firm mass extending from right palate to the midline. A multidisciplinary approach with ENT is required for the surgical treatment. A surgical obturator was made before the surgery, and immediately inserted after with TAD as a retention device. Three months later, a hollow bulb obturator and immediate lower denture was fabricated so the functional capabilities of speech, mastication, deglutition, and esthetics can be restored. Keywords: surgical obturator, maxillofacial prostheses, definitive obturator, hollow bulb